Intellectual need for mathematical knowledge - Miežys, Vytautas (Lietuvos matematikos rinkinys, 2019)
Harel’s [2] notion of intel lectual need is refined by employing Davis’ [1] findingsabout interesting propositions in social sciences. A few hypothetical examples of how thisrevised definition might aid in planning mathematics lessons which provide meaningfulnessfor the students are presented.
Keywords: intellectual need; mathematics education; meaningfulness